THE DEVELOPMENT OF FINANCIAL RISK MANAGEMENT CONCEPTS IN INDONESIAN COMPANIES: A LITERATURE REVIEW - Hety Devita; Muhamad Eko Wahyu Umaryadi; Nurul Huda Yus'an (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the development of financial risk management concepts in Indonesian companies through a literature review. The study traces the transformation of risk management from before the 1997 Asian economic crisis to the era of digitalisation and global market integration. The results of the study show that initially, risk management practices in Indonesia were administrative and reactive. However, the economic crisis triggered a paradigm shift towards the implementation of a more structured and comprehensive risk management system, driven by regulatory policies and the adoption of international standards such as ISO 31000 and the Enterprise Risk Management (ERM) concept. The integration of technology and the development of fintech also presented new challenges, prompting companies to continue strengthening their risk management capabilities. Regulatory support, human resource readiness, and organisational culture are key factors in the successful implementation of financial risk management in Indonesia. Overall, the development of this concept provides an important foundation for companies to enhance their resilience and competitiveness amid the increasingly complex business environment.